Enhanced c-Met activity promotes G-CSF-induced mobilization of hematopoietic progenitor cells via ROS signaling - Tesio, Melania; Golan, Karin; Corso, Simona; Giordano, Silvia; Schajnovitz, Amir; Vagima, Yaron; Shivtiel, Shoham; Kalinkovich, Alexander; Caione, Luisa; Gammaitoni, Loretta; Laurenti, Elisa; Buß, Eike Christian; et al. (Blood, 2011)
Mechanisms governing stress-induced hematopoietic progenitor cell mobilization are not fully deciphered. We report that during granulocyte colony-stimulating factor-induced mobilization c-Met expression and signaling are up-regulated on immature bone marrow progenitors. Interestingly, stromal cell-derived factor 1/CXC chemokine receptor-4 signaling induced hepatocyte growth factor production and c-Met activation. We found that c-Met inhibition reduced mobilization of both immature progenitors and the more primitive Sca-1+/c-Kit+/Lin− cells and interfered with their enhanced chemotactic migration to stromal cell-derived factor 1. c-Met activation resulted in cellular accumulation of reactive oxygen species by mammalian target of rapamycin inhibition of Forkhead Box, subclass O3a. Blockage of mammalian target of rapamycin inhibition or reactive oxygen species signaling impaired c-Met-mediated mobilization. Our data show dynamic c-Met expression and function in the bone marrow and show that enhanced c-Met signaling is crucial to facilitate stress-induced mobilization of progenitor cells as part of host defense and repair mechanisms.
Vorab online veröffentlicht am 28. Juni 2010
Gesehen am 27.10.2022